PENGARUH PARTISIPASI PEMAKAI SISTEM INFORMASI AKUNTANSI, DUKUNGAN MANAJEMEN PUNCAK, DAN PENDIDIKAN DAN PELATIHAN PADA KINERJA SISTEM INFORMASI AKUNTANSI DENGAN KOMPLEKSITAS TUGAS SEBAGAI VARIABEL PEMODERASI - Muliana, I Kadek; Suprasto, Herkulanus Bambang; Ratnadi, Ni Made Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This research was aimed to examine and obtain empirical evidence the effect of user accounting participation information system, top management support, and education on the performance of accounting information system with the complexity of the task as moderating variable. The p lace of research conducted at a banjar’s cooperative in Gianyar regency. The t echniques of data collection using questionnaires. The samples used 60 cooperatives were selected us e the method of sampling non probability with purposive sampling technique . Data analysis techniques use d multiple linear regression analysis moderation regression analysis (MRA) . The results obtained are user participation accounting information systems positive effect on the performance of accounting information systems, top management support positive effect on the performance of accounting information systems, education and training have positive influence on the performance of accounting information systems.
Keywords: Participation Of User, Top Management Support, Education And Training, The Complexityo Of The Task, The Performance